On the evolutionary p-Laplacian equation with a partial boundary value condition - Zhan, Huashui (J Inequal Appl, 2018)
Consider the equation [Formula: see text] where Ω is a bounded domain, [Formula: see text] is the distance function from the boundary ∂Ω. Since the nonlinearity, the boundary value condition cannot be portrayed by the Fichera function. If [Formula: see text] , a partial boundary value condition is portrayed by a new way, the stability of the weak solutions is proved by this partial boundary value condition. If [Formula: see text] , the stability of the weak solutions may be proved independent of the boundary value condition.